Analysis on Spatial Variability of SRM Based on Real-Time CT and the DIC Method Under Uniaxial Loading - Wu, Yanfang; Li, Xiao; Zhang, Luqing; Zhou, Jian; Mao, Tianqiao; Li, Mingtao (Frontiers in Physics, 2022)
Soil and rock mixture (SRM) is consisted of high-strength rock blocks and small-grained soils, which depend seriously on the rock size and the heterogeneity of structure. Because of inhomogeneous cementation between rock blocks, complex granulometric composition, and random distribution of rock blocks, these SRMs usually cause problems. Investigation of the localized deformation is critical for successful engineering designs, engineering safety assessment. In this work, uniaxial compression testing on SRM with a rock block percentage of 40% (mass ratio) is performed under real-time computer tomography (CT) combined with digital image correlation (DIC) technology. Based on radial strain fields and shear fields, heterogeneity of strain fields and rock block motion is analyzed quantitatively by semi-variance. The results show that rock block is the main factor controlling the shear band geometry distribution. Localization strain band usually occurs along the soil and rock interfaces. From the experimental results by DIC method, damage factor is presented to describe the damage evolution of the SRM under uniaxial compression. The method proposed in this study can be used to quantitatively analyze the deformation characteristic of SRM sample.